Digital-Based and Direct Education to Enhance Complementary Feeding Knowledge and Practices: A Systematic Review - Nurati, Okti Eko; Allenidekania, Allenidekania; Waluyanti, Fajar Tri; Rizany, Ichsan (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: The practice of infant and young children still does not meet the WHO guidelines, although different types of education have been carried out to increase mothers' knowledge of infant and young children's feeding practices.Objective: To identify the effectiveness of digital education and direct education in increasing the knowledge and practice of infants and children aged 6-23 months.Method: The research design is a systematic review using PRISMA flow. The databases used to search for articles in English published in the period 2013 to 2023 are Pubmed, ScienceDirect, Scopus, and MEDLINE using the search keywords ‘Mother OR maternal’, ‘Children OR infants’, ‘Digital based AND health education method’, and ‘Complementary feeding’. A total of 461 articles were obtained using RCT, quasi-experiment, and combined RCT-cohort research designs. Researchers use the Covidence tool for the data selection process through the extraction. Risk of bias assessment uses the JBI instrument to evaluate articles.Results: Four articles detail the efficacy of digital-based education (utilizing smartphone applications, WeChat, WhatsApp, and digital job aid education), while five articles delve into the effectiveness of direct education approaches (peer counseling, personalized counseling, and home visits). Another article examines the effectiveness of both home visits and interactive voice calls. The research spanned multiple countries, including Indonesia, Bangladesh, India, China, Cambodia, Iran, and Brazil, encompassing a participant pool ranging from 110 to 1885 research subjects. Findings indicate that digital education enhances mothers’ understanding of nutrition, essential knowledge, practices in providing complementary feeding in line with IYCF guidelines, and mother’s confidence in preparing complementary foods. Moreover, direct education increased compliance with suggested feeding practices, encompassing dietary variety, intake of animal protein, and the consumption of iron-rich foods.Conclusion: Nurses can enhance knowledge and practice of complementary feeding by embracing digital education as a potential solution and concurrently promoting cultural sensitivity and tailored education.